Atypical Lemierre’s syndrome caused by Prevotella oris - Garza Alatorre, Arturo Gerardo; Hernández Rosales, C.; Rodríguez Coronado, J. A.; Solís González, Miriam Cecilia; Balderrama Dávila, Rubén; Rosiles de la Garza, Sara Georgina (UANL. Facultad de Medicina, 2015)
Lemierre’s syndrome is a rare form of severe sepsis secondary to oropharyngeal infection characterized by septic thrombophlebitis of the internal jugular vein with disseminated infections, with the lungs being the most frequent target. We report the case of a previously healthy 15-year-old admitted to the intensive care unit because of septic shock, brain and lung abscesses, and a positive blood culture for Prevotella oris with a clinical presentation compatible with the diagnosis of Lemierre’s syndrome. Conclusion: This is an atypical presentation of Lemierre’s syndrome because of the isolated microorganism.